(3cJGH GdYdd hGdCYQGVs - (3LGdjfhSs
(3ChdgG (B:s
(3GdebGdI GdChdi efg (B( (3jPcQ ajgG GUfGa GdCeQGV (B) s
(3BNQgG (B:s
(3jfJgi CKfGA GdebGdI GdSGOSI , Hbhdg (B( (3aEfi bO bdJ Ef gPG CeQ de jHMK Yfg , hde jaSO GdCWHGA GdeYQhajf HGdeLQHjf , hCfG edJeS Cf CLQHg eGgh (B) s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3hgh cJGH ai GdCTjGA GdNGQLI Yf GdWHjYIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdadSaI hGdefWbs